Brand Image, Price and Product Quality: Determinants Of Consumer Satisfaction - Novianto Eko Nugroho (Makro: Jurnal Manajemen dan Kewirausahaan, 2025)
One of the main challenges faced by the skincare industry in Indonesia is maintaining consumer satisfaction, which refers to consumers’ evaluation of product quality, price, and brand image in line with their expectations. This study aims to analyze the influence of brand image, price, and product quality on customer satisfaction among undergraduate students of the Management Study Program at STIESIA Surabaya who use Avoskin skincare products. In this context, customer satisfaction reflects the level of acceptance and positive experience of consumers toward skincare products, which has implications for loyalty and repurchase intention. This research employs a quantitative descriptive approach, with a finite population consisting of 695 students from the 2017–2020 cohorts. The sample was determined using purposive sampling with the criterion of students who use Avoskin products. Data were collected through a Likert-scale questionnaire measuring brand image, price, product quality, and customer satisfaction, and analyzed using multiple linear regression with the assistance of SPSS version 28. The results indicate that brand image, price, and product quality have a positive and significant effect on customer satisfaction, with brand image being the most dominant variable. These findings highlight the importance of a strong brand image, fair pricing strategies, and consistent product quality in enhancing consumer satisfaction. By understanding the interrelationship among these variables, skincare companies can design more effective marketing strategies to strengthen consumer satisfaction and sustain brand competitiveness in an increasingly dynamic market.